Penerapan Algoritma Apriori Dalam Menentukan Merek Pakaian Yang Paling Diminati Pada Darma Utama - Muhammad Hartono; Fricles A Sianturi (Jurnal Media Informatika, 2023)
Current technological developments in Indonesia are very modern. Currently, in the field of sales, computerized technology is used, one of which is the preparation of goods according to the conditions in which the goods are often sought after by consumers. By utilizing current technology, it will be very easy to spend the stock of goods being sold. The Darma Utama clothing store (DM Fashion) is a sales area that is currently developing, in early 2019 this store was just established and already has its own employees. Various types of clothing, such as dresses, robes, or shirts, are sold under various brands so that they can be in demand by many consumers. However, the impact of sales is competition, where many other shops sell clothes with various types and brands as well as discounts or warehouse cleaning with a price range that is far from the selling price which results in fewer consumers. Data Mining is a combination of data analysis techniques and finding important patterns in the data. In simple terms, it can be defined as the process of selecting, exploring and modeling large amounts of data to find patterns or trends that are usually not recognized. One of the methods in Data Mining is the Apriori Algorithm which searches for frequent itemsets using the Association Rule technique. The a priori algorithm is a type of association rule in data mining. The rules that state the association between several attributes are called affinity analysis or market basket analysis. Association analysis or association rule mining is a data mining technique to find the rules of a combination of items